Peningkatan Gizi Anak Melalui Penyuluhan dan Pembagian Camilan Sehat Jasuke di SDN 035 Tarakan Kelurahan Pamusian Kota Tarakan - Nurul Hidayat; Gatra Aditya Putra; Diva Novianti; Arya Nadani; Martina Murlani; Widya Nur Fita Sari; Nur Indah Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting is a condition where a child experiences growth disorders, so that the child's height does not correspond to his age, as a result of chronic nutritional problems, namely lack of nutritional intake for a long time. One effort that can be made to control stunting is by improving nutrition. Program issued by the government to control stunting in Indonesia. The method used in this activity is education. The results obtained were socialization activities regarding improving children's nutrition through counseling and distribution of healthy snacks (Jasuke). This can be seen from their way of thinking which is increasingly open to implementing activities related to stunting prevention, increasing knowledge in efforts to control stunting through this program. This activity is one of the reference activities carried out by University of Borneo Tarakan students in an effort to prevent stunting cases. This research program aims to improve children's nutrition through education and distribution of healthy snacks. The method used involves promoting balanced nutrition using poster media, as well as distributing healthy, nutritious snacks. This research was conducted on elementary school age children at SDN 035 Tarakan, Pamusian Village RT 19, Jalan Pangeran Antasari, Tarakan City, North Kalimantan Province on September 17 2024.